Response of human bone synthetic under impact loading using experimental method - Mohd Hafeez, Ruslan (2009)
In this report, a method of identifying the absorb energy of bone synthetic is introduced. The method that has been used is impact loading testing. This method provides the properties of bone synthetic in term of the energy that can be slimed in it when subjected to dynamic load. The objective of this project is to investigate the response of bone synthetic under impact load. Experimental design technique was applied in performing the test. 3k full factorial design was used for DOE and DOE table was generated in STATISTICA. The Izod impact load was used to apply load on the specimens and the load range considered were 1 J, 2.75 J and 10.8 J. The additive materials, plastic and metal were included in DOE to identify the material effect on the impact response, so-called absorb energy. Experimental data were analyzed in STATISTICA to develop mathematical model. Deformed specimens were investigated under optical microscope. Statistical analysis shows that the non-linear model is more accurate to predict impact response of bone synthetic. Micrograph indicates that failure pattern of bone synthetic is clear to that of plastic.